ANALISIS KEBIJAKAN PENGELOLAAN OBYEK WISATA TAMAN WISATA MARGASATWA MANGKANG SEMARANG - Tri Yuniningsih (Departemen Administrasi Publik, Universitas Diponegoro, 2015)
UPTD Taman Margasatwa formed based on the mayor 68 Semarangnumber of 2008 , instability visitors is a phenomenon is interesting to checkmanagement has be done by the city Semarang and of tourism city sernarang inits management in support of progress tourism and urban developmentSemarang be increased .In this research focused on the study of analysis policiesthat have been done by of tourism and culture Semarang city especially tourismpark mangkang marga animals , where in the management of taman MargasatwaMangkang Semarang city not maximum .Research aim is to identify the problemis in tourism taman Margasatwa Mangkang Semarang city especially with regardto the physical aspects , formulate alternative policies of physical problems facedby tourism taman Margasatwa Mangkang Semarang city and giverecommendations for alternative.From our observation in the field problems found was there is a lack ofphysical infrastructure, lack of how dare socialization and promotion, the limitedbudget from the government, still relatively low human resources / personnel,there is a lack of quantity human resources, the limited performance employees,duplicate work, there is no special security officers in the game, there is a lack ofthe trash, park did not yet have good, job desk employees who are clear, thathas not been the management of zoo mangkang, still low public participation /visitors in maintaining healthy, income have not reached a designatedtarget.Formulation alternative policies that is recommended after conductedstage weighting and scoring, so three alternative policies delivered thecoordination with third party private and, improvement of infrastructure, andchanges of form the uptd to other forms.In order to overcome problems , so the management tourism tamanMargasatwa Mangkang Semarang city must be responsiveness and responsive toeverything possible , so that we can remain in existence and could be an icontourism in central java , continuously improve cooperation with all partiesconcerned in order to attract tourists , local as well as foreign .As with biginvestors / private , travel agencies and hotels and mass media , improvement ofinfrastructure in the tourist attraction taman Margasatwa Mangkang Semarangcity , that have attraction , security and visitors .Keywords : policy analysis; managing; Mangkang Zoo